CONTRIBUTION A LA CARACTERISATION MORPHOMETRIQUE DES OVINS EXPLOITES DANS LA REGION DE SOUK-AHRAS ET OUM EL-BOUAGH - Khaoula,BENSEMCHA; Massaouda,BOUDEBOUZ (My University, 2022)
Our study is a statistical analysis on the morpho-baymetric characters of sheep breeds exploited in the regions of Souk Ahras and Oum el Bouaghi including: The average height (HG) of 79.75 ± 5.50 cm; an average body length (LSI) of 83.73 ± 9.69 cm and a chest circumference (TP) of 101.13 ± 08.82 cm on average. These three measures have very high variance values , which explains the variability in the population. The other measurements: ear width (Ola), barrel perimeter (Pc), head length (tL), head width (tla) and ear length (oL) have very low variance values. The biometric measurements of the sheep breeds studied vary with sex. Significant differences were observed at 0.001 between males and females for the characters HG, LSI, TP, HP, LE, LH, LB, TL, tl, Pc (P<0.001). Finally, depending on the region, that of Oum el Bouaghi is lower than that of the Souk Ahras. دساعخُا ػباسة ػٍ ححهُم إحصائٍ نهصفاث انشكهُت وانبُى يخشَت نغالالث األغُاو انًغخغهت فٍ يُطقخٍ عىق أهشاط وأو انبىاقٍ بًا فٍ رنك: يخىعط االسحفاع 5.50 ± 79.75 (HG (عى؛ َبهغ يخىعط طىل انجغى 9.69 ± 83.73 (LSI (عى ويحُط انصذس 010101 ± 18180 عى فٍ انًخىعط. ححخىٌ هزِ انًقاَُظ انزالرت ػهً قُى حباٍَ ػانُت جذًا يًا َفغش انخباٍَ فٍ انًجخًغ. انقُاعاث األخشي: ػشض األرٌ (ola (ويحُط انبشيُم (Pc (وطىل انشأط (tL (وػشض انشأط (tla (وطىل األرٌ (oL (نها قُى حباٍَ يُخفضت جذًا. حخخهف انقُاعاث انبُى يخشَت نغالالث األغُاو انخٍ حًج دساعخها حغب انجُظ. نىحظج فشوق راث دالنت إحصائُت ػُذ 11110 بٍُ انزكىس واإلَاد فٍ األحشف HG ، LSI، TP، HP، LE، LH، LB، TL، tl، .)0.001 <P (Pcوأخُشًا، اػخًادًا ػهً انًُطقت، فإٌ يُطقت أو انبىاقٍ أقم يٍ يُطقت عىق األهشط. Notre étude est une analyse statistique sur les caractères morpho-baymétrique des races ovines exploitées dans les régions de souk ahras et Oum el Bouaghi dont : La hauteur (HG) moyenne de 79,75±5,50 cm ; une longueur de corps (LSI) moyenne de 83,73±9,69 cm et un tour de poitrine (TP) de 101,13 ±08,82 cm en moyenne. Ces trois mesures ont des valeurs de variance très élevés ce qui explique une variabilité dans la population. Les autres mesures : la largeur de l’oreille (ola), le périmètre du canon (Pc), la longueur de tête (tL), la largeur de la tête (tla) et la longueur de l’oreille (oL) ont des valeurs de variance très faible. Les mesures biométriques des races ovines étudiées varient avec le sexe. On observe des différences significatives à 0,001 entre les mâles et les femelles pour les caractères HG, LSI, TP, HP, LE, LH, LB, TL, tl, Pc (P<0,001). Et enfin selon la région celle d’Oum el Bouaghi inferieur à celle des Souk Ahras.